Evaluación de desempeño al personal del departamento administrativo financiero del gobierno provincial de Loja. - Belizaca Yaguana, Tatiana del Cisne (2012)
This research shows the process of implementing the system performance evaluation based on standard performance evaluation coded according to the reforms of Resolution No. SENRES-2008-00170 issued by the National Technical Secretariat of Human Resources Development and Sector Wages Public (SENRES), now called the Ministry of Labour Relations. The Labor Ministry shows through your website design an automated form called MRL-EVAL-01, the same as a general indicator for purposes of performance evaluation was applied to officials and Provincial Government Loja. This instrument MRL-EVAL-01, is composed of different metrics that allowed us to evaluate the effectiveness, knowledge, skills, values and organizational culture, observable behaviors such as teamwork, initiative and leadership factors that helped analyze the organizational environment officials and servants of the Provincial Government of Loja. For the implementation of the evaluation process of direct supervisors, with the support and training of Human Resource Management Unit, established the necessary space for the assessor together with an interview to determine correctly at the beginning of the evaluation period established activities essential job, their indicators and the number of activities to meet by the assessed, at the end of the evaluation period immediate supervisors perform the qualification process for entering numerical values or choosing default factors that exist in automated form to enter data automatically become percentage, thus determining the qualification attained evaluated by the server as a result of performance evaluation. The ratings in accordance with the provisions of Article 22 of the standard performance evaluation are: excellent, very good, satisfactory, poor and unacceptable. Determined by the percentage rating as follows: Excellent. - High Performance, whose rating was achieved less than 90.5%. Very good. - Performance better than expected, a rating that is between 80.5% and 90.4%. Satisfactory. - Expected performance rating that is between 70.5% and 80.4%. Poor. - Performance lower than expected, a rating that is between 60.5% and 70.4%. Unacceptable. - Very low performance expected, rating or below 60.4%. As results of the performance evaluation conducted staff administrative and financial departments of the Provincial Government of Loja, rating scales reached by most servers are between excellent, very good and satisfactory grades that according to Article 23 of standard performance evaluation, called the purposes of performance evaluation, are considered in the incentive plan and have preference for promotions or career development and enhancement of their skills. This also determines the target 1in the development of this research by conducting a survey to servers and administrative official sand financial departments in order todeterminethe inventoryof personnel andto submit it to the Provincial Institution. Associated with the above findings and identifies a series of recommendations that could be useful for successful management of human resources in the Loja Provincial Government, through the performance evaluation, trying to make definite that every organization must adapt the recommendations set if believed relevant according to their interests or purpose of the same, according to the activity and the objectives pursued.